SOME USEFUL ACTIVITIES IN TEACHING SPEAKING IN FOREIGN LANGUAGES AT THE BEGINNER LEVEL - Abdurakhmonova Makhfuza Olimovna (Лучшие интеллектуальные исследования, 2023)
Annotation: The problems of modernization of the modern education system, insufficient development of theoretical and practical issues of teaching foreign languages have determined the need to identify ways to overcome difficulties in teaching non-linguistic students to speak a foreign (English) language in a group with different basic levels of training. The task facing the foreign language teacher of the university is to select and use the methods of teaching speaking, which make it possible to adapt and improve the basic knowledge of a foreign language among students for successful communication. The analysis of scientific and pedagogical works of scientists allowed to form the basic principles of teaching students to speak a foreign language.